In vitro detection of hepatitis C virus in platelets from uninfected individuals exposed to the virus - Padovani, Juliana Lara; Corvino, Silvia Maria; Drexler, Jan Felix; Silva, Giovanni Faria [UNESP]; Pardini, Maria Ines de Moura Campos [UNESP]; Grotto, Rejane Maria Tommasini [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2013)
Introduction ,,,,,Despite hepatocytes being the target cells of hepatitis C virus (HCV), viral ribonucleic acid RNA has been detected in other cells, including platelets, which have been described as carriers of the virus in the circulation of infected patients. Platelets do not express cluster differentiation 81 CD81, the main receptor for the virus in hepatocytes, although this receptor protein has been found in megakaryocytes. Still, it is not clear if HCV interacts with platelets directly or if this interaction is a consequence of its association with megakaryocytes. The aim of this study was to evaluate the interaction of HCV with platelets from non-infected individuals, after in vitro exposure to the virus. ,,,, ,,,, ,,,,,Methods ,,,,,Platelets obtained from 50 blood donors not infected by HCV were incubated in vitro at 37°C for 48h with serum containing 100,000IU∕mL of genotype 1 HCV. After incubation, RNA extracted from the platelets was assayed for the presence of HCV by reverse transcription – polymerase chain reaction RT-PCR. ,,,, ,,,, ,,,,,Results ,,,,,After incubation in the presence of virus, all samples of platelets showed HCV RNA. ,,,, ,,,, ,,,,,Conclusions ,,,,,The results demonstrate that, in vitro, the virus interacts with platelets despite the absence of the receptor CD81, suggesting that other molecules could be involved in this association.
Keywords: HCV; Platelets; CD81